2019
DOI: 10.1038/s41598-019-45764-1
|View full text |Cite
|
Sign up to set email alerts
|

Varroa destructor parasitism has a greater effect on proteome changes than the deformed wing virus and activates TGF-β signaling pathways

Abstract: Honeybee workers undergo metamorphosis in capped cells for approximately 13 days before adult emergence. During the same period, Varroa mites prick the defenseless host many times. We sought to identify proteome differences between emerging Varroa -parasitized and parasite-free honeybees showing the presence or absence of clinical signs of deformed wing virus ( DWV ) in the capped cells. A label-free proteomic analysis utilizing nanoLC couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 176 publications
(233 reference statements)
3
33
1
Order By: Relevance
“…In this study, the suppression of caspase3-like , caspase8-like , and caspase9-like in DWV-injected honeybee pupae was investigated at 96 h. We suggested that this virus might block apoptosis pathways despite the downregulation of transcripts encoding Buffy, which is Bcl-2-like pro-survival protein displaying anti-apoptotic and cell cycle inhibitory functions [ 21 , 62 , 63 ]. Similarly, Erban et al in 2019 reported that anti-apoptotic Bcl-2 transcripts were downregulated in DWV-infected honeybees and Varroa -infested bees with visible DWV symptoms [ 26 ]. The p53 gene has also been demonstrated to downregulate Bcl-2 protein and triggered apoptosis cascades [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the suppression of caspase3-like , caspase8-like , and caspase9-like in DWV-injected honeybee pupae was investigated at 96 h. We suggested that this virus might block apoptosis pathways despite the downregulation of transcripts encoding Buffy, which is Bcl-2-like pro-survival protein displaying anti-apoptotic and cell cycle inhibitory functions [ 21 , 62 , 63 ]. Similarly, Erban et al in 2019 reported that anti-apoptotic Bcl-2 transcripts were downregulated in DWV-infected honeybees and Varroa -infested bees with visible DWV symptoms [ 26 ]. The p53 gene has also been demonstrated to downregulate Bcl-2 protein and triggered apoptosis cascades [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Koziy et al suggested that apoptosis occurred in the hypopharyngeal gland cells of DWV-infected newly emerged honeybees [ 23 ]. Although immune and apoptosis-related gene responses to the virus were investigated in several studies [ 5 , 24 , 25 , 26 ], information on the temporal relationship between DWV levels and these genes is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, parasited bees have a lower sugar responsiveness and a faster habituation to olfactory stimulation [52]. Moreover, Varroa provokes the down-regulation of immune gene expression in emerging infested adults [45], as well as proteomic changes in the honey bee's immune response [53][54][55]. It disrupts the bee's immune response by interfering in the cascade immune response [56].…”
Section: What Can It Do?mentioning
confidence: 99%
“…Nevertheless, many of these proteins have been noted as responsive to honey bee parasitism. Notably, Apidermin-3 like protein has recently been implicated as an outlier protein suppressed by DWV but induced by Varroa parasitism in a proteome study [18]. In that report Apidermin appears to be down-regulated by DWV infection, but up-regulated by Varroa and DWV+Varroa.…”
Section: Genes Strongly Down-regulated In R_virus V S_virus Injectedmentioning
confidence: 87%